Perceptions of football analysts goal-scoring opportunity predictions: a qualitative case study - Aguado-Méndez, R. D.; González-Jurado, J. A.; Reina-Gómez, Á.; Otero-Saborido, F. M. (Frontiers in Psychology, 2021)
This study aimed to understand the way tactical football analysts perceive the general match analysis issues and to analyze their tactical interpretation of the predictive models of conceded goal-scoring opportunities. Nine tactical analysts responded to the semi-structured interviews that included a general section on the match analysis and a specific one on the results of a study on goal-scoring opportunities conceded by a Spanish La Liga team. Following their transcription, the interviews were codified into categories by the two researchers using Atlas Ti® software. Subsequently, frequency count and co-occurrence analysis were performed based on the encodings. The content analysis reflected that analysts play a crucial role in the analysis of their own team and that of the opponent, the essential skills to exercise as a tactical analyst being "understanding of the game" and "clear observation methodology." Based on the case study of the conceded goal-scoring opportunities, the major causes and/or solutions attributed by analysts in some of the predictive models were the adaptability of the "style of play" itself according to the "opponent" and "pressure after losing."